2017
DOI: 10.1093/europace/eux250
|View full text |Cite
|
Sign up to set email alerts
|

Intra-atrial re-entrant tachycardia in congenital heart disease: types and relation of isthmus to atrial voltage

Abstract: In our population with a high proportion of complex CHD, CTI-related IART was the most frequent mechanism, although non-CTI-related IART was present in 49% of patients (alone or with concomitant CTI-related IART). A cut-off voltage of 0.5 mV could identify 95.4% of the substrates in non-CTI-related IART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Entrainment and concealed fusion could be studied in 95.7% of the patients. Areas of scar were delineated from peak‐to‐peak amplitude of a bipolar electrogram, using a cut‐off value of 0.5 mV . During ablation, temperature and power were limited to 43°C and 30 to 40 W for irrigated‐tip catheter (81% of the procedures) and 60°C to 70°C and 60 to 70 W for no cooled catheter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Entrainment and concealed fusion could be studied in 95.7% of the patients. Areas of scar were delineated from peak‐to‐peak amplitude of a bipolar electrogram, using a cut‐off value of 0.5 mV . During ablation, temperature and power were limited to 43°C and 30 to 40 W for irrigated‐tip catheter (81% of the procedures) and 60°C to 70°C and 60 to 70 W for no cooled catheter.…”
Section: Methodsmentioning
confidence: 99%
“…Areas of scar were delineated from peak-to-peak amplitude of a bipolar electrogram, using a cut-off value of 0.5 mV. 30 During ablation, temperature and power were limited to 43°C and 30 to 40 W for irrigated-tip catheter (81% of the procedures) and 60°C to 70°C and 60 to 70 W for no cooled catheter. Ablation success was defined as termination of IART and noninducibility of any kind of IART for all patients.…”
Section: Electrophysiological Studymentioning
confidence: 99%
“…Our cohort demonstrated the comparable of atrial tachyarrhythmia mechanisms in CHD, with predominant IART through the cavo‐annular (cavo‐tricuspid) isthmus. In cases of non‐CTI‐related IART, the most frequent location of IART isthmus was the lateral or posterolateral wall of the venous atria . Recurrent circuits around caval orifices, crista terminalis, or the atrial appendage are also observed, but less frequently .…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Roca‐Luque et al, a cut‐off voltage of 0.5 mV could identify 95.4% of the substrates in non‐CTI‐related IART . Unexcitable sites can be displayed together with the caval veins, valve annuli, and lines of double potentials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation